The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s12885-015-1114-3
|View full text |Cite
|
Sign up to set email alerts
|

The significance of the co-existence of osteopontin and tumor-associated macrophages in gastric cancer progression

Abstract: BackgroundOsteopontin (OPN) can recruit macrophages to the site of inflammation and promote tumorigenesis. M2 tumor-associated macrophages (M2-TAMs) also play an important role in cancer progression. This study aimed to clarify the role of OPN and M2-TAMs co-existence in gastric cancer.MethodsThe levels of OPN and M2-TAMs were evaluated by immunohistochemical staining in 170 resected gastric cancer specimens that were collected from 1998 to 2012. M2-TAMs were identified by staining for an M2 marker, CD204. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 32 publications
(30 reference statements)
1
59
0
Order By: Relevance
“…Dimethyl sulfoxide can suppress mouse 4T1 breast cancer growth by modulating TAM differentiation [133]. It was found that PA-MSHA can reeducate CD163 + TAMs into M1 macrophages through the TLR4-mediated pathway in MPE [27]. M-CSFR signaling was found to govern the phenotype of M2-like MHC-II lo TAMs, and its blockade results in preferential differentiation of monocytes into M1-like MHC-II hi TAMs [134].…”
Section: Treatments Targeting Tamsmentioning
confidence: 99%
“…Dimethyl sulfoxide can suppress mouse 4T1 breast cancer growth by modulating TAM differentiation [133]. It was found that PA-MSHA can reeducate CD163 + TAMs into M1 macrophages through the TLR4-mediated pathway in MPE [27]. M-CSFR signaling was found to govern the phenotype of M2-like MHC-II lo TAMs, and its blockade results in preferential differentiation of monocytes into M1-like MHC-II hi TAMs [134].…”
Section: Treatments Targeting Tamsmentioning
confidence: 99%
“…We confirmed the trametinib-driven decrease in osteopontin secretion in separate ELISA experiments (Figure 7B). We focused on osteopontin because it has been reported to induce MDSCs expansion (25) and tumor recruitment of macrophages (24). Supporting the relevance of our proteomic analysis, the tumor-driven increase of osteopontin in plasma was abrogated by short-term (3 day) treatment with trametinib in Brpkp110-bearing mice (Figure 7C).…”
Section: Resultsmentioning
confidence: 99%
“…Among these, osteopontin has been implicated in the recruitment of macrophages into tumors (23) and its expression is positively correlated with CD204 + M2-like macrophages (24). Osteopontin secreted by tumor cells has also been reported to drive the expansion of MDSCs in the spleens of tumor-bearing mice through activation of the ERK1/2-MAPK pathway in myeloid progenitors (25).…”
Section: Introductionmentioning
confidence: 99%
“…In gastric cancer, TAM infiltration is associated with phenotypes such as angiogenesis, depth of invasion, and nodal status that characterize aggressive malignancies. High infiltration of TAMs conferred a poor prognosis in gastric cancer after resection (7,8). The invasiveness of gastric cancer cells could be enhanced by coculture with TAMs (8).…”
Section: Introductionmentioning
confidence: 99%
“…High infiltration of TAMs conferred a poor prognosis in gastric cancer after resection (7,8). The invasiveness of gastric cancer cells could be enhanced by coculture with TAMs (8). However, the way in which TAMs promote gastric tumorigenesis remains unclear.…”
Section: Introductionmentioning
confidence: 99%